gem-Difluorovinyl and trifluorovinyl Michael acceptors in the synthesis of α,β-unsaturated fluorinated and nonfluorinated amides - Monika Bilska-Markowska; Marcin Kaźmierczak; Wojciech Jankowski; Marcin Hoffmann (Beilstein Journal of Organic Chemistry)
The incorporation of fluorine atoms within the structure of organic compounds is known to exert a significant impact on their electronic properties, thereby modulating their reactivity in diverse chemical transformations. In the context of our investigation, we observed a striking illustration of this phenomenon. A Michael addition involving gem-difluorovinyl and trifluorovinyl acceptors was successfully achieved, demonstrating high stereoselectivity. This selectivity was further elucidated through theoretical calculations. Using this methodology, a series of new α,β-unsaturated amides, both fluorinated and nonfluorinated, were synthesized.